Calcium channel blockers are associated with improved survival and lower cardiovascular mortality in patients with renovascular disease. Issue 6 (4th December 2018) - Deshmukh, Harshal; Barker, Emma; Anbarasan, Thineshkrishna; Levin, Daniel; Bell, Samira; Witham, Miles D.; George, Jacob
Summary: Background and objective: Results of interventional trials in renovascular hypertension have been disappointing, and medical therapy is the current recommended gold standard. However, the comparative long‐term benefits of different antihypertensive drug classes in atherosclerotic renal artery stenosis are not known. We aim to assess the effect of different antihypertensive drug classes on outcomes in renovascular hypertension Design, setting, participants, and measurements: Using Tayside Health Informatics Centre database, anonymized data over a 6‐year period was analyzed. Biochemistry, prescribing data, morbidity, mortality, and demographic data were accessed via hospital medical records and electronic data stored in the Tayside Health Informatics Centre Safe Haven. General Registrar's Office data were used to identify patients who died from cardiovascular disease. Independent predictors of survival in each group were analyzed using Kaplan‐Meier survival curves and Cox proportional hazard models, adjusted for a range of covariates, using time‐updated drug analysis. Blood pressure data were obtained from primary and secondary care clinic blood pressure records for each patient. Adjustments for mean systolic blood pressure over the follow‐up period and baseline blood pressure were made. Results: A total of 579 patients with atherosclerotic renal artery stenosis were identified. In the unilateral renal artery stenosis cohort, calcium channel blockers but not ACE inhibitors/ARBs were associated with a significant reduction in all‐cause (HR = 0.45, CI = 0.31, 0.65; P = <0.0001) and cardiovascular (HR = 0.51, CI = 0.29‐0.90 P = 0.019) mortality. This was maintained after adjustment for blood pressure. In the bilateral renal artery stenosis cohort, both classes of drugs reduced all‐cause but not cardiovascular mortality. Patients with moderate disease benefitted more than those with mild or severe disease. Conclusions: Calcium channel blockers are associated with significantly increased survival and lower cardiovascular mortality particularly in patients with moderate RAS disease.